Low Serum Dehydroepiandrosterone Is Associated With Diabetic Kidney Disease in Men With Type 2 Diabetes Mellitus - Zhang, Xinxin; Xiao, Jinfeng; Li, Xin; Cui, Jingqiu; Wang, Kunling; He, Qing; Liu, Ming (Frontiers in Endocrinology, 2022)
Abstract Background: The associations of dehydroepiandrosterone (DHEA) and dehydroepiandrosterone sulfate (DHEAS) with diabetic kidney disease (DKD) remained unclear. Thus, this cross-sectional study aimed to explore the associations of DHEA and DHEAS with the risk of DKD in patients with T2DM. Methods: The information of 1251 patients with T2DM were included in this study. Serum DHEA and DHEAS were quantified using liquid chromatography-tandem mass spectrometry assays. Multivariate logistic regression analyses were used to assess the associations of DHEA and DHEAS with DKD as well as high urine albumin to creatinine ratio (ACR). Results: In men with T2DM, the risk of DKD decreased with an increasing DHEA concentration after adjustment for traditional risk factors; the fully adjusted OR (95% CI) for tertile3 vs tertile1 was 0.37 (0.19-0.70; P = 0.010 for trend). Similarly, when taking high ACR as the outcome, low DHEA levels were still significantly associated with increased odds of high ACR (OR, 0.37; 95% CI, 0.19–0.72 for tertile3 vs tertile1; P = 0.012 for trend). The restricted cubic spline showed that the risk of DKD gradually decreased with the increment of serum DHEA levels (P-overall = 0.007; P-nonlinear = 0.161). DHEAS was not independently associated with the risk of DKD and in men. In contrast, no significant relationships were found between DHEA and DHEAS and the risk of DKD in women (all P > 0.05). Conclusions: In men with T2DM, low serum DHEA levels were independently related to the risk of DKD after adjustment for traditional risk factors. Our finding highlights the potential role of DHEA in the development of DKD in men with T2DM.